Extreme citizen science: Lessons learned from initiatives around the globe. Issue 2 (23rd December 2021) - Chiaravalloti, Rafael Morais; Skarlatidou, Artemis; Hoyte, Simon; Badia, Marcos Moreu; Haklay, Muki; Lewis, Jerome
Abstract: The participation of communities living in high conservation value areas is increasingly valued in conservation science and practice, potentially producing multiple positive impacts on both biodiversity and local people. Here, we discuss important steps for implementing a successful extreme citizen science project, based on four case studies from conservation projects with Pantaneiro fishers living in Brazilian Pantanal wetland, Baka hunter‐gatherers and Fang farmers in lowland wet forest in Cameroon, Maasai pastoralists in Kenya, and Ju|'hoansi rangers living in the semiarid deserts of Namibia. We highlight the need for a high level of trust between the target communities and project developers, communities' right to choose the data they will be collecting, and researchers' openness to include new tools that were not initially planned. By following these steps, conservation scientists can effectively create bottom‐up collaborations with those living on the frontlines of conservation through community‐led extreme citizen science. Abstract : Extreme citizen science is a powerful approach in conservation practice. Here, we present important steps for practitioners aiming to using it.